(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
The electricity sector has many challenges, one of them is related to the use of systems with a high level of reliability and availability, because customers have become more dependent on electricity, for instance: engage new transnational companies that seek to establish operations in the country, provide statistical data to improve business administration, improve customer satisfaction, among others. This research included the use of sensors in a smart grid to detect faults in less time (depending on its location and amount). The results obtained from the investigation were a better monitoring of the medium voltage grid electrical variables, an efficient reaction time due to the segmentation of the route’s grid, savings in unsold energy, and others. It was found that the recovery period of the initial investment is less than a 10 years period, and a sensitivity analysis was executed in which the preliminary economic viability of the project was presented.